Association Between Access to Oral Health Information and Use of Fluoride Toothpaste with at Least 1000 PPM in Peruvian Children - Eunji Oh-Aguilar; María Claudia Garcés-Elías; Neila C. Quiroz-Silva; Jesely H. Torres-Ramirez; Roberto A. León-Manco (Odovtos - International Journal of Dental Sciences, 2026)
Oral health education is assumed to improve knowledge and behaviors regarding fluoride toothpaste use. However, dental caries prevention requires comprehensive strategies that integrate dental examinations, provision of fluoride toothpaste, and preventive treatments.To analyze the association between access to oral health information and the use of fluoride toothpaste with a concentration of ≥1000 ppm in Peruvian children under 12 years of age. A cross-sectional analysis was conducted using nationally representative 2023 ENDES data, including 23,613 children. Independent variables were access to oral health information and its provider; the dependent variable was fluoride toothpaste use (≥1000 ppm). Covariates included wealth index, natural region, health insurance, altitude, area and place of residence, age, and sex. Multilevel Poisson regression estimated prevalence ratios (PR) and 95% confidence intervals (CI).In bivariate analyses, appropriate fluoride toothpaste use was significantly associated with information provider (p